Physiotherapeutic rehabilitation of patients with traumatic orthopedic diseases of the lower limbs in the postoperative period: A literature review (Research, Society and Development, 2026)
This study addresses physiotherapeutic rehabilitation in the postoperative period of traumatic orthopedic diseases affecting the lower limbs, highlighting its importance in functional recovery and improvement of patients’ quality of life. The objective is to investigate the relevance of physiotherapy in this process, analyzing the main resources, techniques, and outcomes related to motor recovery, prevention of complications, and promotion of patient autonomy.This is a descriptive literature review with a qualitative approach, developed through the analysis of scientific publications from 2021 to 2025. The bibliographic search was conducted in the PubMed database, using standardized descriptors in English based on DeCS/MeSH vocabularies, combined through Boolean operators.The results demonstrate that physiotherapy plays an essential role in postoperative rehabilitation, significantly contributing to improvements in mobility, muscle strength, and functional independence. The main interventions include therapeutic exercises, kinesiotherapy, gait training, aquatic physiotherapy, and specific techniques such as blood flow restriction. Additionally, early physiotherapeutic intervention proved to be crucial in reducing complications, shortening hospital stay, and improving clinical outcomes.It is concluded that physiotherapeutic care is fundamental in the recovery process of patients with traumatic orthopedic impairments of the lower limbs and should be conducted in an individualized manner, based on scientific evidence.